Nanostructured materials based on mesoporous silica and mesoporous silica/apatite as osteogenic growth peptide carriers - Mendes, L. S. [UNESP]; Saska, S. [UNESP]; Martines, M. A U; Marchetto, Reinaldo [UNESP] (Elsevier, 2013)
The aim of this work was the preparation of inorganic mesoporous materials from silica, calcium phosphate and a nonionic surfactant and to evaluate the incorporation and release of different concentrations of osteogenic growth peptide (OGP) for application in bone regeneration. The adsorption and release of the labeled peptide with 5,6-carboxyfluorescein (OGP-CF) from the mesoporous matrix was monitored by fluorescence spectroscopy. The specific surface area was 880 and 484 m2 g- 1 for pure silica (SiO) and silica/apatite (SiCaP), respectively; the area influenced the percentage of incorporation of the peptide. The release of OGP-CF from the materials in simulated body fluid (SBF) was dependent on the composition of the particles, the amount of incorporated peptide and the degradation of the material. The release of 50% of the peptide content occurred at around 4 and 30 h for SiCaP and SiO, respectively. In conclusion, the materials based on SiO and SiCaP showed in vitro bioactivity and degradation; thus, these materials should be considered as alternative biomaterials for bone regeneration. © 2013 Elsevier B.V.
Keywords: Controlled release; Mesoporous silica; Osteogenic growth peptide; Bone regeneration; Degradation of the material; In-vitro bioactivity; Mesoporous matrix; Mesoporous Silica; Osteogenic growth peptides; Simulated body fluids; Biological materials; Biomaterials; Fluorescence spectroscopy; Mesoporous materials; Nonionic surfactants; Silica; Peptides